VIOLÊNCIA DE GÊNERO E RELIGIÃO: UMA ANÁLISE DA INFLUÊNCIA DO CRISTIANISMO EM RELAÇÕES FAMILIARES VIOLENTAS A PARTIR DE MULHERES ACOLHIDAS NAS CASAS ABRIGO REGIONAL GRANDE ABC E DE HOMENS AUTORES DE VIOLÊNCIA DOMÉSTICA - OSHIRO, CLAUDIA MARIA POLETI (2017)
Domestic violence is a worrying phenomenon. In a concrete or symbolic way, it pervades the daily lives of many women who have experienced domestic violence situations. Once socially constructed, man is placed in an unequal position of power, these actions are often trivialized and reinforced by a society that is marked by patriarchy. Gender inequalities reinforce violence against women. My practice shows that many of these women seek help in religion, more specifically with their religious leaders who, in addition to agreeing with the violence that woman has lived, reinforce it through their religious beliefs. The cases seen at Casas Abrigo Regional Grande ABC attest that many women do not break the violence cycle because they belong to some religious institution and hear from their leaders discourses that legitimize submission and violence against women. This research intends to identify and analyze the Christianity influence in the violent family relations of Catholic and Evangelical women hosted in Casas Abrigo Regional Grande ABC and the same religious groups' perpetrators of violence against women. We will try to understand the violence consequences in these women's life, as well as to identify religion's influence in the masculine exercise of aggression and in the subjection of women to aggression. To approach these women, we chose two Reference Centers for Women's Care: “Marcia Dangremon” and “Vem Maria” as a field of this research. In order to approach the perpetrators of violence against women, we chose Centro de Referência Especializado de Assistência Social – CREAS de São Bernardo do Campo.